Identification of novel gut microbiota-related biomarkers in cerebral hemorrhagic stroke - Fengli Ye; Huili Li; Hongying Li; Xiue Mu (Frontiers in Medicine)
IntroductionHemorrhagic stroke, especially intracerebral hemorrhage (ICH), is the most fatal type of stroke and a major cause of mortality and disability. Due to ambiguous symptoms and limited biomarkers, early diagnosis and prognosis remain challenging. Recent evidence suggests that gut microbiota dysregulation influences neuroinflammation and outcomes in ICH, but the underlying molecular mechanisms remain unclear.MethodsTranscriptome data from the GSE24265 dataset were analyzed to identify differentially expressed genes (DEGs) in ICH. Gut microbiota-related genes (GMRGs) were obtained from GeneCards and literature, and overlapping genes were defined as gut microbiota-related DEGs (GMRDEGs). Functional enrichment, gene set enrichment analysis (GSEA), and protein–protein interaction (PPI) analyses were performed. Hub genes were screened using LASSO, RandomForest, and SVM-RFE algorithms. Validation was conducted in plasma samples from ICH patients (n=20) and controls (n < 20) by qRT-PCR, and in a collagenase-induced ICH mouse model. The therapeutic effect of fecal microbiota transplantation (FMT) was evaluated through neurological scoring, hematoma volume, brain edema, intestinal barrier protein expression, inflammatory cytokines, and hub gene expression.ResultsWe identified 806 DEGs in ICH, among which 65 overlapped with GMRGs. These GMRDEGs were enriched in immune processes and pathways such as TNF and IL-17 signaling. PPI network analysis highlighted IL1B, IL6, and CCL2 as central nodes. Machine learning identified four hub genes—LEF1, ITGAX, BLVRB, and ATF4. All were significantly upregulated in ICH tissues and plasma, correlating with immune cell infiltration. In vivo, FMT reduced hematoma volume and brain edema, improved neurological function, restored intestinal barrier proteins, decreased inflammatory cytokines, and downregulated hub gene expression.DiscussionLEF1, ITGAX, BLVRB, and ATF4 were identified as gut microbiota-related biomarkers of ICH. Their modulation by FMT highlights the role of the brain–gut axis in ICH and suggests potential diagnostic biomarkers and therapeutic targets.